2018
DOI: 10.1002/lary.27415
|View full text |Cite
|
Sign up to set email alerts
|

Vocal Hygiene Education Program Reduces Surgical Interventions for Benign Vocal Fold Lesions: A Randomized Controlled Trial

Abstract: 1b Laryngoscope, 2593-2599, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 23 publications
1
18
0
1
Order By: Relevance
“…A control group and an experimental intervention group (vocal education and vocal hygiene program) were compared. After 2 months of follow-up, a significantly higher resolution rate was observed in the intervention group (61.3% Vs 26.3%), suggesting that – even if a certain rate of spontaneous resolution can be observed, voice therapy programs have a role in affecting the outcome in a positive way 18 .…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…A control group and an experimental intervention group (vocal education and vocal hygiene program) were compared. After 2 months of follow-up, a significantly higher resolution rate was observed in the intervention group (61.3% Vs 26.3%), suggesting that – even if a certain rate of spontaneous resolution can be observed, voice therapy programs have a role in affecting the outcome in a positive way 18 .…”
Section: Discussionmentioning
confidence: 88%
“…Nevertheless, some authors highlighted that VFPs can sometimes resolve without surgery thanks to conservative treatments. Some studies suggest that voice rest, programs of voice hygiene and voice therapy can be effective in treating some vocal folds polyps 18 , 19 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result was similar to the previous studies. [7,18] As the muscle tone and the size of the vocal cord nodule decrease with voice therapy, glottal closure improves and the MPT increases.…”
Section: Discussionmentioning
confidence: 99%
“…If these fail, then surgery is considered. [7] It has been shown that vocal cord nodules can decrease in size or disappear with voice therapy. [8][9][10] However, according to our clinical experience, vocal cord nodules persist after voice therapy while the symptoms resolve.…”
mentioning
confidence: 99%